A Survey On Frequency Of Defensive Medicine Among General Practitioners Of Kerman City - Mohammadreza Amiresmaili; Mahmood Nekoueimoghadam; Mahmood Moosazadeh; Fatemeh Esmaili; Mahboobeh Mirtajeddini (Tehran University of Medical Sciences, 2014)
Background and Aim: Defensive medicine is a potential social problem which can bring about consequences for public health regarding the quality of personal care and wastage of limited health resources. In this study, the frequency of positive and negative defensive medicine behaviors was examined among general practitioners of Kerman city.  Materials and Methods: This cross-sectional study was conducted among general practitioners in the city of Kerman. As data collection instrument, a questionnaire was given to a sample of 100 subjects. The obtained data were entered into SPSS 20 and analyzed using such descriptive statistics as frequency percentage and mean, and applying analytical tests such as chi-square and t-test.  Results: In this research, 100 general practitioners were studied. The frequency of positive and negative defensive medicine behavior was 99% and 47%, respectively. Besides, the positive defensive medicine behavior in men was more than that in women (100% vs. 97.2%); on the contrary, the negative defensive medicine behavior in women was more than that in men (52.8% vs. 43.8%). Explaining in more detail about taking medicines properly and on time and avoiding the prescription of risky behaviors which might be useful to patients had the highest frequency among positive and negative defensive medicine behaviors, respectively.  Conclusion : The present study showed that the frequency of defensive medicine was high in the studied population and that the application of factors related to this phenomenon by the participants of the present study was prevalent.